(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2024)
This study examines the relationship between the type of reader the informants consider themselves to be and the lexis available both in Spanish and in the first foreign language. The sample consists of 270 Primary Education pupils from five public schools in the province of Málaga. Six centers of interest were selected, and a sociological questionnaire and an associative test based on lexical availability, as defined by the PPHDL, were applied. Results showed that students who like reading contribute more words in the second and third cycles in both Spanish and foreign languages. Furthermore, it was observed that, as the cycle progresses, students lose their enjoyment of reading. This work has implications for the teaching of reading, urging the planning of texts and activities to extend vocabulary in both languages. Likewise, the establishment of reading itineraries and the planning of specific vocabulary acquisition activities are encouraged and can be framed within the different plans and programs offered by educational administrations.